The Effect of Family-Centered Empowerment Program on Self-Efficacy of Adolescents with Thalassemia Major: A Randomized Controlled Clinical Trial - Leili Borimnejad; Soroor Parvizy; Hamid Haghaani; Belgheis Sheibani (Shiraz University of Medical Sciences, 2018)
Background: Chronic nature of thalassemia causes changes in different aspects of life in patients, including their self-efficacy. The aim of this study was to determine the effect of family-centered empowerment program on the self-efficacy of adolescents with Thalassemia major. Methods: A quasi-experimental study was performed on adolescents with thalassemia major in 2013 in Bandar Abbas, Iran. The participants were divided into intervention and control groups, respectively. Research instruments included demographic data questionnaire, need assessment self-made questionnaire, general self-efficacy scale, and sickle cell self-efficacy scale. After collecting the data from the pre-intervention step, family-centered empowerment program was implemented for the intervention group and secondary test was conducted six weeks after the intervention and the results were analyzed by statistical SPSS-21 software, using independent t-test, paired t-test, Chi-square and Fisher's exact test, and descriptive statistics. A significance level of P<0.05 was considered as significant. Results: The mean and standard deviation of the adolescents' age were 16±1.9 in the intervention group and 15.2±2 in the control group. Independent t-test showed a significant difference between the two groups after the intervention for both self-efficacies (P<0.01 and P=0.02). In the control group, the results of general self-efficacy scores after six weeks' time were reduced compared to the previous one while disease-related self-efficacy scores in the same group after six weeks' time increased and paired t-test indicated a significant difference in the mean scores for both self-efficacies in both groups. Conclusion: Implementation of family-centered empowerment program for patients with thalassemia major is practically feasible and it can increase self-efficacy in these patients. It is suggested that the program should be used in comprehensive care protocols of children and adolescents. Trial Registration Number: IRCT201407211788N8